Fattening Management Of Skinny Bali Catle Variety (Bos Sondaicus) By Utilization Of Agricultural Waste And Local Plant In Sumbawa - Aris Sugiarto; Mega Trishuta Pathiassana; Ahmad Yamin (UNIVED Press, Dehasen University Bengkulu, 2022)
Sumbawa is one area that has the potential to be developed as a center for beef cattle production which is quite competitive in Indonesia. The proportion of cattle in Sumbawa itself is around 21% which is generally dominated by the Bali cattle variety (Bos sondaicus). Therefore, a business that has great potential to support this goal is cattle fattening. Unfortunately, one of the main problems encountered in fattening cattle is the cost of feed. Thus, the management of Bali cattle fattening that utilizes agricultural waste for the manufacture of feed is urgently needed. In addition, the management of fattening cattle must also be complemented by other components, such as the manufacture of medicines to treat diseases of underweight Bali cattle using local plants, the process of bathing, drying, and monitoring the cattle to be fattened. From the research and observations conducted, it is known that the time needed to get the cow display condition with ideal characteristics and optimal weight in the fattening process is 3 months. During this time, the selling price of lean fattened cows increased by about 2-2.3 times. It can be concluded, that the fattening management of lean Bali cattle carried out in Pungka Village, Unter Iwes District, Sumbawa Regency is quite profitable. In addition, this can also be used as part of community waste management that is integrated with community livestock business.